Pengaruh Kecepatan Spindle dan Feed Rate Terhadap Kekuatan Sambungan Las Tipe Friction Stir Welding Untuk Aluminium Seri 1100 Dengan Tebal 2 MM - Prabowo, Azhar Faris; , Agus Dwi Anggono, ST, M.Eng, Ph.D; , Muh. Alfatih H, ST, MT (2016)
The aims of the research are to determine the strength of aluminum welded joints by using friction stir welding method, the hardness distribution by micro vickers, macro and micro structure, and to determine the optimum spindle speed and feet rate. In this research, the base metal was aluminum alloy sheet plate with a thickness of 2 mm. The welding process was conducted by using friction stir welding (FSW) method. That was done in a variety of spindle speed and feed rate. To investigate the weld strengt, a tensile test was performed by using standard ASTM E8, ASTM E384 standard for hardness test and ASTM E3 / E7 for micro and macro photos. The results shows that the highest tensile strength was 75.01 MPa and 77.57 MPa. That values were obtained from tensile testing of welding angle direction of 0˚ and 45˚, using parameters of 1600 rpm spindle speed and feed rate of 10 mm / min. Micro vickers testing on the retreating side area has a higher hardness than the advancing side. Investigations of the macro image was delivered the welding defects in the specimen 1 and 2 , while specimens 3 and 4 were showed in good results. Photo micro of nugget zone was showed the microstructure changes of base metal due to the material deformation during stiring process. Based on the experiments, the welding process by using the parameters of 1600 rpm spindle speed and feed rate of 10 mm / min were delivered the best welded aluminium.